Protocol to collect causal chain data on agriculture adaptation effectiveness and resilience - Nowak, Andreea Cristine (2025)
This working paper introduces a conceptual model and operational protocol for assessing adaptation effectiveness and resilience in agricultural systems through explicit causal chains linking climate shocks, adaptive actions, mediating processes, and outcomes. Building on a rich literature on resilience, vulnerability, and adaptation measurement, it addresses persistent fragmentation in the evidence base, where different parts of the adaptation process are often analyzed in isolation. The paper presents a structured model and two complementary tools—a household survey module and a participatory focus group guide—that enable the collection of relational, event-anchored data across shocks, actions, and effects. Applied within the accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project, the protocol demonstrates how these tools can operationalize complex impact pathways without imposing new data burdens. The novelty of this effort lies in providing a coherent causal structure that connects actions, mechanisms, and outcomes over time; integrating monitoring, evaluation, and impact assessment efforts within a single logic; and bridging empirical and experiential evidence to generate a dynamic, cumulative understanding of how adaptation produces resilience across contexts and timescales.